BIOTERRORISM: Life Science-Plant Microbiology - P.GAJALAKSHMI (International Journal of Life Science and Pharma Research, 2012)
Bioterrorism is a criminal act against unsuspecting civilians using pathogenic biological agents, such as biological warfare agents. Bioterror and Biological Warfare agents are most often colorless, by-and-large odorless microorganisms (bacteria, viruses, fungi) or toxins (usually protein toxins) derived from microorganisms that can be spread in air as aerosols or in food or drink to infect as many people as possible. They are easily concealed, and thus difficult to detect before an attack. Their main advantages to terrorists are allowing easy escape and causing panic and chaos within a civilian population. Their aim is to overwhelm emergency medical departments at local hospitals and clinics. However, there are ways to help protect yourself against bioterror agents and by extrapolation biological warfare agents and to help identify an attack when it occurs